Seycehelles : Welfare Impacts of Exchange Rate Adjustment and Policy Options - Kojo, Naoko C.; Ivaschenko, Oleksiy (World Bank, Washington, DC, 2015)
This paper studies likely macroeconomic impacts and social consequences of devaluation of the Seychelles rupee. Analyzing potential welfare impacts of devaluation ex ante is crucial for policy making, since information obtained from such analyses would allow policy makers to design cost-effective, well-targeted policy measures, with the aim of mitigating negative social consequences of devaluation. Based on the estimated welfare impact of devaluation, the paper considers mitigation policy options, and discusses their effectiveness and associated budgetary costs. The focus of this study is the likely impacts of devaluation on the prices, economy and social welfare. The reminder of the paper is structured as follows. Section two first analyzes Seychelles’ household expenditure survey data and presents the incidence of poverty and inequality in Seychelles. Section three then discusses how the Seychelles economy would adjust to an initial devaluation of the US dollar value of the rupee by 45 percent, followed by a gradual move to an equilibrium level. Projected macroeconomic variables and prices are applied to the household survey data to estimate possible impacts on the incidence of poverty. Section four discusses a variety of policy measures designed to alleviate the adverse impacts on the poor. Fiscal viability of these measures is also discussed in this section. Section five concludes the paper.